Hydrogen generation from solid state NaBH4 by using FeCl3 catalyst for portable proton exchange membrane fuel cell applications. (12th July 2019) - Boran, Aslı; Erkan, Serdar; Eroglu, Inci
Abstract: Being a boron-based compound, sodium borohydride, NaBH4, is a convenient hydrogen storage material for applications like unmanned air vehicles. There are several concerns behind commercialization of hydrogen gas generator by NaBH4 hydrolysis systems. This study aims to contribute to the solution of the problems of NaBH4 hydrolysis system in three main ways. First, the usage of solid state NaBH4 enables to increase the durability and the gravimetric H2 storage capacity of the system in order to meet US DOE targets. Second, solid NaBH4 usage decreases the system's weight since it does not require a separate fuel storage tank, which is very important for portable, on demand applications. Finally, the system's cost is decreased by using an accessible and effective non-precious catalyst such as ferric chloride, FeCl3 . The maximum hydrogen generation rate obtained was 2.6 L/min and the yield was 2 L H2 /g NaBH4 with an efficiency of 76% at its most promising condition. Moreover, the novel solid NaBH4 hydrogen gas generator developed in the present work was integrated into a proton exchange membrane fuel cell and tested at the optimum operating conditions. Highlights: Hydrogen is produced on demand by injecting water to solid NaBH4 . Hydration factor plays an important role in hydrogen generation rate. The system's cost is decreased by using ferric chloride as catalyst. Hydrogen generation reactor is integrated to a single PEM fuel cell. Hydrogen energy system developed can be used as a portable power generator.